Intestinal Microbes in Patients With Schizophrenia Undergoing Short-Term Treatment: Core Species Identification Based on Co-Occurrence Networks and Regression Analysis - Xiang, Min; Zheng, Liqin; Pu, Daoshen; Lin, Feng; Ma, Xiaodong; Ye, Huiqian; Pu, Daoqiong; Zhang, Ying; Wang, Dong; Wang, Xiaoli; Zou, Kaiqing; Chen, Linqi; et al. (Frontiers in Microbiology, 2022)
As a common mental disease, schizophrenia has a huge impact of health and economic on global people. Evidence is growing that the microbiota-gut-brain axis provides an important pathway for the interaction of gut microbiota and schizophrenia development. However, it is not clear how changes in gut microbiota composition and function during antipsychotic treatment improve symptoms of schizophrenia. Here, 25 patients with schizophrenia were recruited and collected their fecal samples before and after treatment in hospital for 14 days. 16s rRNA sequencing and analysis were conducted to evaluate the gut microbiota composition and function, which results showed fecal microbiota was significant differences between before and after treatment. And Firmicutes (a relative abundance of 82.60% and 86.64%) and Gemminger (a relative abundance of 14.17% and 13.57%) were the first dominant species at the phyla and genus level. Furtherly, after fecal microbiota transplantation, the antibiotic-treated recipient mice performed multiple behavioral improvement such as decreased psychomotor hyperactivity, increased social interaction and memory. The random forest algorithm and co-occurrence network analysis demonstrated that intestinal flora (especially the key species, ASV57) as biomarkers may be used to clarify the pathology of clinical presentations and match treatment options accordingly. In conclusion, this study suggests that the differences in the composition of gut microbiota after treatment is related to the development and severity of schizophrenia and may provide a potential target in the treatment of this disorder.